Outcomes of transforaminal epidural injection of amniotic membrane/umbilical cord particulate for lumbar radiculopathy: a case series - Miedema, Mark; Anderson, Angela (Frontiers in Pain Research, 2024)
Background Radiculopathy can be a debilitating condition. Amniotic membrane/umbilical cord (AM/UC) particulate is a relatively new injectable treatment modality. Herein we report the outcomes of epidural injection of AM/UC particulate in managing lumbar radiculopathy. Methods Consecutive patients with lumbar radiculopathy who received epidural injection of AM/UC particulate for lumbar radiculopathy were included. Primary outcome was change in pain as measured by the 11-point numerical rating scale. Safety was assessed by AM/UC- and procedure-related complications. Paired t-tests were used to determine statistical significance. Results A total of 12 patients with a mean age of 56.7 ± 21.0 years were included in the analysis. The patients were previously treated with physical therapy (91.7%), chiropractic corrective measures (16.7%), epidural steroid injection (83.3%), and radiofrequency ablation (8.3%). Two patients (16.7%) were taking opioids for chronic pain syndrome. After AM/UC injection, the average pain score decreased from 6.6 ± 1.5 to 5.2 ± 1.9 at 1–3 months, 2.0 ± 1.4 at 6 months, and 2.9 ± 1.4 at last mean follow-up of 21.3 ± 11.1 months (p < 0.001). No patients required subsequent treatment or surgery. There were also no complications. Conclusion This case series supports the preliminary safety and shows potential benefit of epidural AM/UC particulate injection in this cohort of patients with lumbar radiculopathy pain.